Ion heating and energy balance during magnetic reconnection events in the RFX-mod experiment. (4th January 2022) - Gobbin, M.; Agostini, M.; Auriemma, F.; Carraro, L.; Cavazzana, R.; Fassina, A.; Franz, P.; Marrelli, L.; Momo, B.; Piovan, R.; Predebon, I.; Puiatti, M.E.; et al.
Abstract: Reconnection events in high current reversed field pinch plasmas are often associated to the partial or total loss of the helical magnetic topology. The electron temperature collapse during these phenomena is investigated in RFX-mod thanks to high time resolution soft-x-ray diagnostics; these data are used, together with magnetic energy reconstructions, for energy balance analysis. The paper shows that the energy released during reconnection events, similarly to astrophysical plasmas, might be involved in ion heating, the latter being estimated by the energy distribution function of neutral atoms, a rather interesting feature in a reactorial perspective. These issues will be further investigated in RFX-mod2 , an upgrade of the present device starting its operations from 2022, where the modified boundary conditions are expected to increase the helical states duration and reduce the frequency of reconnection events.